Effects of tumor necrosis factor on undifferentiated and syncytialized placental choriocarcinoma BeWo cells. (April 2022) - Eliesen, Gaby A.M.; Fransen, Milou; Kooijman, Nina; van den Broek, Petra H.H.; Russel, Frans G.M.; Greupink, Rick
Abstract: Tumor necrosis factor (TNF) regulates trophoblast turnover during the formation of the placental syncytium and can be a potentially relevant target for adverse effects of xenobiotics. We mimicked syncytialization in vitro by stimulating BeWo cells with 50 μM forskolin. Undifferentiated and syncytialized BeWo cells were exposed to TNF (10 pg/mL–10 ng/mL) for 48 h after which cell viability, progesterone release and gene expression of a selected set of markers representative for placental function were assessed. In undifferentiated BeWo cells, high TNF levels (1–10 ng/mL) increased gene expression of TNF, NF-κB, and TNFRSF1B to maximally 99 ± 17, 2.2 ± 0.2, and 3.0 ± 0.4 of control values, respectively ( p  < 0.001). These effects were also found in syncytialized BeWo cells but less pronounced. Additionally, TNF may induce syncytialization in BeWo cells as it upregulated ERVW-1 expression by 1.55 ± 0.14-fold ( p  < 0.05). On the contrary, TNF levels of 10 and 100 pg/mL did not affect gene expression in both undifferentiated and syncytialized BeWo cells, but did enhance cell viability in syncytialised BeWo cells ( p  < 0.001). In conclusion, we found that high TNF levels (1–10 ng/mL) increased gene expression of TNF, NF-κB, and TNFRSF1B especially in undifferentiated BeWo cells, while physiological TNF concentrations positively affected cell viability and while there was no effect on any of the investigated functional markers. Highlights: Physiological TNF levels upregulated cell viability in syncytialised BeWo cells. Physiological TNF levels did not affect progesterone release in BeWo cells. Physiological TNF levels did not affect gene expression of placenta function markers in BeWo cells. High levels of TNF induce gene epression of syncytialisation and TNF signaling markers in BeWo cells.